STRATEGI KOMUNIKASI PEMASARAN GRAND MALL BEKASI DALAM MENCAPAI SASARAN PASAR BARU MIDDLE UP - Danik Isnawati; Saepudin . (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2014)
To be able to submit the value to the customer, the process required to create, communicate and manage relationships in a way that is mutually beneficial. It needs a strong strategy and tactics to be able to market their goods or services according to the target. Marketing is done to create positive and effective stimulant to match the target. Marketers and consumers are the two things that were instrumental in marketing so need to understand one another. Need for an innovative combination between practice, theory, and current marketing concepts marketing process to run effectively. Grand Mall Bekasi is one mall in Jakarta which is located on the main street Of Jakarta, JL. Jend. Sudirman, Medan Satria. Such case showed that Grand Mall Bekasi have strategic places which can be utilized to be business opportunities. Therefore, Grand Mall Bekasi have concepts, strategies, methods, and ways to developing the business to reach new target markets middle up